Uma investigação sobre o ensino e aprendizagem de funções logarítmicas através da utilização da modelagem matemática assistida pela programação do app inventor - Alves, Cassy Jones Florencio (2022)
This research aimed to investigate the teaching and learning process of logarithmic functions through the use of mathematical modeling assisted by the MIT App Inventor programming. platform in which it has its programming language in blocks available for free online. In addition, App Inventor offers the possibility to create applications, granting creation and testing. The methodology used in the research, in relation to the approach to the problem, was used qualitative research. In relation to the objectives, the exploratory format was used, and in relation to its technical procedures, it was characterized as a case study. Two pedagogical workshops were carried out, comparing analytical modeling with modeling and programming, whose sample size was 62 undergraduates from the Mathematics Degree Course at the Federal University of Paraíba - Campus IV. Regarding the results, significant results were observed, for the union of 2 methodologies for a learning purpose, revealing that it is possible to review modeling processes through programming and intensify each step, through the process of computational thinking. In addition, it was possible to observe that by adding the idea of computational thinking and programming as an implement to mathematical modeling, it promoted the experimentation of automatism, providing an opportunity to review the model formulation processes from a logical and technological point of view, which makes the modeling possible with exactitude and mathematical rigor, giving rise to the perspective of complementing the modeling steps with the programming, and thus evidencing its potential and synergy. What comes to arouse the student's interest, for the possibilities of interpretation and use, to understand the phenomena and problem situations, and to solve them, by the application created from the model.